DESIGNING LISTENING DIGITAL BOOK FOR 2ND GRADE JUNIOR HIGH SCHOOL - Fatimatuzahroh, Siti; Agustina, Ulfa Wulan (Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to design a Learning Media 'Listening Digital Book' which focuses on 2nd Grade Junior High School students in learning English at Mts Al-Islam Genengan. The type of research used is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This media has been validated by 2 experts before being tested on students, there are material experts and media experts. The researcher collect data using a questionnaire that given to students. The implementation results obtained were 96.2% in the